2012
DOI: 10.1016/j.marpolbul.2012.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plankton concentration on gametogenesis and spawning of the black lip pearl oyster Pinctada margaritifera in Ahe atoll lagoon (Tuamotu archipelago, French polynesia)

Abstract: Pearl culture industry represents one of the dominant business sector of French Polynesia. However, it still entirely relies on unpredictable spat collection success. Our aim was to assess the influence of natural plankton concentration fluctuations on maturation and spawning of the black lip pearl oyster Pinctada margaritifera, during a 4 months survey conducted in Ahe atoll lagoon. Plankton concentration was assessed by chlorophyll a extraction and by microscope counts while gonadic index, gonado-visceral dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 45 publications
4
29
0
Order By: Relevance
“…Besides temperature, food availability is also affecting broodstock energy reserves and gametogenesis in bivalves (Baghurst and Mitchell 2002, Frias and Segovia 2009, Fourniera et al 2012. In this investigation, chlorophyll a and organic matter amounts were recorded as very high in the Homa Lagoon and levels are probably sufficient for the onset of gametogenesis and gonad development throughout the year.…”
Section: Discussionmentioning
confidence: 60%
“…Besides temperature, food availability is also affecting broodstock energy reserves and gametogenesis in bivalves (Baghurst and Mitchell 2002, Frias and Segovia 2009, Fourniera et al 2012. In this investigation, chlorophyll a and organic matter amounts were recorded as very high in the Homa Lagoon and levels are probably sufficient for the onset of gametogenesis and gonad development throughout the year.…”
Section: Discussionmentioning
confidence: 60%
“…Better knowledge of factors controlling recruitment variability will also enable to better understand the wild populations structure and to rationalise a collecting strategy for aquaculture. In particular, gametogenesis, spawning and larval growth potential also determine spat collection variability (Fournier et al, 2012;Thomas et al, 2012). Coupling biology and physic-based approaches is now needed to perpetuate the pearl oyster aquaculture.…”
Section: Consequences For Spat Collectionmentioning
confidence: 99%
“…food concentration and/or availability). Indeed, Fournier et al (2012) showed recently that P. margaritifera developed a clear opportunistic strategy of reproduction in which gametogenesis rate and spawning are directly related to plankton concentration, itself correlated to the wind speed.…”
Section: Bivalve Larvae Patterns Related To Environmental Factorsmentioning
confidence: 99%
“…In addition, abundances were negatively correlated with the distance from the eastern reef, which could partly be related to hydrodynamic effects on retention or through the effect of the compensatory current in deep layers . At last, the large scale heterogeneity in larval concentration may be related to the trophic resource heterogeneity described by Thomas et al (2010) and the opportunistic strategy of reproduction of P. margaritifera described by Fournier et al (2012), with higher plankton concentration close to the east and west reefs, corresponding to the sectors most concentrated in larvae. On the smallest scales, larval abundances were significantly correlated with temperature, salinity and food concentration, and exhibited vertical swimming behaviour leading to vertical structuring of abundances.…”
Section: Bivalve Larvae Patterns Related To Environmental Factorsmentioning
confidence: 99%